Comparison of bioconcentration factor of heavy metals between endemic fish and aquacultured fish in Maninjau Lake, West Sumatra, Indonesia - Puti Sri Komala; Restu Maulida Azhari; Febi Yulia Hapsari; Tivany Edwin; Taufiq Ihsan; Zulkarnaini Zulkarnaini; Mustika Harefa (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Komala PS, Azhari RM, Hapsari FY, Edwin T, Ihsan T, Zulkarnaini, Harefa M. 2022. Comparison of bioconcentration factor of heavy metals between endemic fish and aquacultured fish in Maninjau Lake, West Sumatra, Indonesia. Biodiversitas 23: 4026-4032. Fish have a high risk of accumulating metals and poses a risk of entering human bodies through the food chain. This study aims to analyze the concentration of lead (Pb), mercury (Hg), and cadmium (Cd) spatially and temporally as well as the Bioconcentration Factor (BCF) in endemic fish (Rasbora argyrotaenia) and aquacultured fish (Oreochromis niloticus) in Maninjau Lake and its relationship to environmental parameters (pH, DO and temperature). Sampling was conducted at domestic, hydropower, fish cage, and endemic fisheries. Spatial and temporal distribution using one-way ANOVA with 95% significance, while parameter correlation using linear regression. Almost all heavy metals in both fish samples exceeded the permissible level except in endemic fisheries sites. Metal concentrations in both fish species spatially showed a significant difference, while temporally showed no significant difference. Rasbora argyrotaenia showed a slightly higher BCF value than O.niloticus. The BCF values were low accumulative with order Pb>Hg>Cd ??in R. argyrotaenia and Pb>Cd>Hg for O. niloticus. There is a strong and positive correlation between temperature and the BCF value of both fish species for the three different metals. Monitoring fish by keeping metal content within acceptable limits is necessary. Further research on risk analysis of fish consumption in humans is recommended.